Adjuvant chemotherapy and relative survival of patients with stage II colon cancer – A EURECCA international comparison between the Netherlands, Denmark, Sweden, England, Ireland, Belgium, and Lithuania. (August 2016) - Breugom, A.J.; Bastiaannet, E.; Boelens, P.G.; Iversen, L.H.; Martling, A.; Johansson, R.; Evans, T.; Lawton, S.; O'Brien, K.M.; Van Eycken, E.; Janciauskiene, R.; Liefers, G.J.; et al.
Abstract: Background: The aim of the present EURECCA international comparison is to compare adjuvant chemotherapy and relative survival of patients with stage II colon cancer between European countries. Methods: Population-based national cohort data (2004–2009) from the Netherlands (NL), Denmark (DK), Sweden (SE), England (ENG), Ireland (IE), and Belgium (BE) were obtained, as well as single-centre data from Lithuania. All surgically treated patients with stage II colon cancer were included. The proportion of patients receiving adjuvant chemotherapy was calculated and compared between countries. Besides, relative survival was calculated and compared between countries. Results: Overall, 59, 154 patients were included. The proportion of patients receiving adjuvant chemotherapy ranged from 7.1% to 29.0% (p < 0.001). Compared with NL, a better adjusted relative survival was observed in SE (stage II: relative excess risks (RER) 0.53, 95% confidence interval (CI) 0.44–0.64; p < 0.001), and BE (stage II: RER 0.84, 95% CI 0.76–0.92; p < 0.001), and in IE for patients with stage IIA disease (RER 0.80, 95% CI 0.65–0.98; p = 0.03). Conclusion: The proportion of patients with stage II colon cancer receiving adjuvant chemotherapy varied largely between seven European countries. No clear linear pattern between adjuvant chemotherapy and adjusted relative survival was observed. Compared with NL, SE and BE showed an improved adjusted relative survival for stage II disease, and IE for patients with stage IIA disease only. Further research into selection criteria for adjuvant chemotherapy could eventually lead to individually tailored, optimal treatment of patients with stage II colon cancer. Highlights: Use of adjuvant chemotherapy for stage II colon cancer varies largely across Europe. No clear pattern between use of adjuvant chemotherapy and relative survival was found. Sweden and Belgium had better adjusted relative survival compared with Netherlands. Ireland had better adjusted relative survival for stage IIA compared with Netherlands.